Business intelligence applied in buildings energy efficiency - Pinheiro, L. (2021)
This article deals with the application of business intelligence, data visualization tools, to analyze the improvement of energy efficiency in residential buildings in Portugal. We used an exploratory data method, which was obtained from the Energy Agency (ADENE), applying business intelligence systems for historical analysis and drawing up projections until the year 2035. The results obtained showed energy inefficiency in Portuguese housing buildings, with approximately 44% of them classified with energy certification D, E, and F. We created a scenario with the goal of raising these homes to at least energy classification C, as recommended by the study carried out by the Committee on Climate Change of the United Kingdom. This time, we identified that several benefits would be achieved, from reducing the value of the electricity bill to reducing the emission of greenhouse gases.